Controversy over the Obligation of Professional Zakat for Civil Servants from the Perspective of Maqashid Syariah - Muhammad Ali; Pagar Pagar; Mhd Yadi Harahap (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2026)
The discourse on the obligation of professional zakat for civil servants continues to be a hot topic of debate in Indonesia, both from the perspective of government regulations and contemporary fiqh discourse. This study aims to analyse the roots of the controversy surrounding the obligation of professional zakat for ASN and review it through the lens of Maqashid Syariah. The main focus of this study is to evaluate whether the policy of automatically deducting ASN salaries for zakat is in line with the basic objectives of sharia, namely to realise maslahah (benefit) and reject mafsadah (harm). The research method used is qualitative with a library research approach. Primary data is sourced from MUI Fatwa Number 3 of 2003 concerning Income Zakat and related government regulations, while secondary data is obtained from classical and contemporary literature on professional zakat. The results of the study show that the controversy arises from differences of opinion regarding the qiyas (analogy) used; whether professional zakat is analogous to gold zakat (due to the nature of the property) or agricultural zakat (due to the harvest time). On the one hand, those who require it argue that professional zakat is a form of social justice. On the other hand, those who oppose it highlight the legal uncertainty regarding the limits of nishab and haul, which have not been agreed upon absolutely in classical texts. Through the perspective of Maqashid Syariah, this study finds that the obligation of professional zakat for civil servants strongly supports the elements of Hifz al-Mal (protection of wealth) on a public scale and Hifz al-Nafs (protection of life) for the mustahik through wealth redistribution. However, its implementation must maintain the principles of voluntariness and transparency so as not to harm the interests of civil servants who have different financial burdens. This study concludes that legal certainty regarding professional zakat requires not only regulatory legitimacy, but also a deep understanding of the objectives of equitable social welfare. Harmonisation between state policy and sharia principles is necessary so that professional zakat is not seen as a double tax burden, but rather as an effective and sustainable instrument for poverty alleviation in Indonesia.